Linkage Disequilibrium and Haplotype Homozygosity in Population Samples Genotyped at a High Marker Density (2006)
ABSTRACT: Objective: Analyze the information contained in homozygous haplotypes detected with high density genotyping. Methods: We analyze the genotypes of ∼2,500 markers on chr 22 in 12 population samples, each including 200 individuals. We develop a measure of disequilibrium based on haplotype homozygosity and an algorithm to identify genomic segments characterized by non-random homozygosity (NRH), taking into account allele frequencies, missing data, genotyping error, and linkage disequilibrium. Results: We show how our measure of linkage disequilibrium based on homozygosity leads to results comparable to those of R2, as well as the importance of correcting for small sample variation when evaluating D′. We observe that the regions that harbor NRH segments tend to be consistent across populations, are gene rich, and are characterized by lower recombination. Conclusions: It is crucial to take into account LD patterns when interpreting long stretches of homozygous markers.